mTORC1 and mTORC2 regulate skin morphogenesis and epidermal barrier formation - Ding, Xiaolei (Nat Commun, 2016)
Mammalian target of rapamycin (mTOR), a regulator of growth in many tissues, mediates its activity through two multiprotein complexes, mTORC1 or mTORC2. The role of mTOR signalling in skin morphogenesis and epidermal development is unknown. Here we identify mTOR as an essential regulator in skin morphogenesis by epidermis-specific deletion of Mtor in mice (mTOR(EKO)). mTOR(EKO) mutants are viable, but die shortly after birth due to deficits primarily during the early epidermal differentiation programme and lack of a protective barrier development. Epidermis-specific loss of Raptor, which encodes an essential component of mTORC1, confers the same skin phenotype as seen in mTOR(EKO) mutants. In contrast, newborns with an epidermal deficiency of Rictor, an essential component of mTORC2, survive despite a hypoplastic epidermis and disruption in late stage terminal differentiation. These findings highlight a fundamental role for mTOR in epidermal morphogenesis that is regulated by distinct functions for mTORC1 and mTORC2.